2010
DOI: 10.1111/j.1365-2249.2010.04294.x
|View full text |Cite
|
Sign up to set email alerts
|

Older age of rheumatoid arthritis onset is associated with higher activation status of peripheral blood CD4+ T cells and disease activity

Abstract: SummaryRheumatoid arthritis (RA) is a chronic inflammatory disease, with a clinical manifestation both systemic and in joints. It has been suggested that age at disease onset and/or patients' age have influence on disease activity and clinical outcome. The reasons for the different course of RA in older people are not known; however, the activation status of peripheral blood lymphocytes could be responsible. Our aim was to relate expression of activation markers in peripheral blood CD4 + T cells of RA patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
(35 reference statements)
4
21
0
1
Order By: Relevance
“…As inferred from the current study, most of arthritis patients are above 60 years of age, and similar results were found on a study done by Pawlowska et al [13].…”
Section: Discussionsupporting
confidence: 93%
“…As inferred from the current study, most of arthritis patients are above 60 years of age, and similar results were found on a study done by Pawlowska et al [13].…”
Section: Discussionsupporting
confidence: 93%
“…Our study also suggested that the percentage of activated T cells was higher in the MNCs from RA patients than controls after stimulation with anti-CD3 + anti-CD28, which was consistent with a previous clinical study [27]. Abnormal T cell functions were well characterized in patients with RA [28].…”
Section: Discussionsupporting
confidence: 92%
“…Demographic data: In the present study, the RA patients age ranged from 30 to 50 years with mean age was (42.6) years, this matches the mean age in the study of (Ramos-Remus et al, 2002) [6].The total number of the female patients was 76 (89.4%) which is higher than the total number of males, which was 9 (10.6%), this resembles the gender distribution in other studies [2,4,7].…”
Section: Ivdiscussionmentioning
confidence: 48%